The Feel of the City : Experiences of Urban Transformation - Kenny, Nicolas, 1977- (Book collections on Project MUSE., 2014)
"The Feel of the City exposes the sensory experiences of city-dwellers in Montreal and Brussels at the turn of the century and the ways in which these shaped the social and cultural significance of urban space. Using the experiences of municipal officials, urban planners, hygienists, workers, writers, artists, and ordinary citizens, Nicolas Kenny explores the implications of the senses for our understanding of modernity."--Publisher's website